ANALISIS KEGAGALAN IMPLEMENTASI SISTER CITY ANTARA KOTA YOGYAKARTA DAN KATHMANDU - M Saifullah; Raden Roro Kinthana Amodya Kusuma; Winona Albertha; Nur Assyahida Surya; Zahra Zamaya; Setyo Pratiwi, Tiffany (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2026)
Paradiplomacy is a form of foreign cooperation implemented by sub-state entities or local governments, whether provincial, district, or city. This form of paradiplomacy cooperation takes the form of sister cities, which aim to promote cooperation, cultural exchange, trade, and student exchanges, oriented towards specific regional objectives. In 2023, the City of Yogyakarta, through the Minister Counselor for Political Functions of the Indonesian Embassy (KBRI) in Dhaka, initiated a recommendation for Yogyakarta to establish a sister-city relationship with Kathmandu, Nepal, focusing on arts, culture, and tourism. However, as of this writing, there has been no concrete implementation of this cooperation initiative. This will then become the focus of this research, namely analyzing the factors that contributed to the failure of the sister city implementation between the City of Yogyakarta and Kathmandu in 2023 through the implementation gap theory. This research uses a qualitative descriptive method with literature studies as the primary data source, and interviews with the Yogyakarta City Cultural Office as supporting data. The research findings indicate a weak commitment between the cooperation initiative and its implementation between the central and regional governments. Coordination between government sub-actors is one of the main factors contributing to the failure of the cooperation.